Biomimetic organization: Octapeptide self-assembly into nanotubes of viral capsid-like dimension - Valéry, Céline (National Academy of Sciences, 2003)
The controlled self-assembly of complex molecules into well defined hierarchical structures is a promising route for fabricating nanostructures. These nanoscale structures can be realized by naturally occurring proteins such as tobacco mosaic virus, capsid proteins, tubulin, actin, etc. Here, we report a simple alternative method based on self-assembling nanotubes formed by a synthetic therapeutic octapeptide, Lanreotide in water. We used a multidisciplinary approach involving optical and electron microscopies, vibrational spectroscopies, and small and wide angle x-ray scattering to elucidate the hierarchy of structures exhibited by this system. The results revealed the hexagonal packing of nanotubes, and high degree of monodispersity in the tube diameter (244 Å) and wall thickness (≈18 Å). Moreover, the diameter is tunable by suitable modifications in the molecular structure. The self-assembly of the nanotubes occurs through the association of β-sheets driven by amphiphilicity and a systematic aromatic/aliphatic side chain segregation. This original and simple system is a unique example for the study of complex self-assembling processes generated by de novo molecules or amyloid peptides.